CLONING, EXPRESSION AND PURIFICATION OF RECOMBINANT ANALOG OF TAQ DNA POLYMERASE - Abeldenov, S.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2014)
Polymerase chain reaction (PCR) is a method that is used in solving of many molecular biology problems. At the beginning of PCR development the DNA-polymerase from Escherichia coli was used for amplification of DNA segments. After discovery of DNA-polymerase from Thermus aquaticus (Taq-polymerase) this enzyme due to its thermostability is widely used in PCR for DNA amplification. Taq-polymerase is highly thermostable DNA-polymerase. Nowadays this is the most commonly used enzyme in polymerase chain reaction and DNA sequencing. In this article we describe a procedure for obtaining the recombinant Taq-polymerase, including steps of cloning the gene and its expression in a heterologous environment, as well as the purification of recombinant enzyme. Gene of Taq-polymerase was cloned into expression vector. The identity of cloned gene was confirmed by sequencing. Analysis of nucleotide sequence showed that recombinant Taq-polymerase consists of 852 amino acid residues (including 20 additional amino acids at N-terminus that contain 6xHis-tag) and has a molecular mass of 96 kDa. The recombinant protein has been purified, characterized and showed polymerase activity and thermostability. Despite availability of a variety of commercial sources of thermostable DNA polymerases from bacteria genus Thermus, the most widely used enzyme is Taq DNA polymerase. However enzymes for molecular biology are not produced in Kazakhstan, and therefore, organization of recombinant enzymes production for use in research and diagnostic practice is an important and urgent task. The expression system and purification method used in this article allow obtaining sufficient amount of the recombinant enzyme - Taq DNA-polymerase.